The Correlation Between Student’s Perception on Teacher using Second Language in Teaching English with Student’s Motivation on Learning English - Qomariyah, Nur Laili; Arifani, Yudhi (Universitas Muhammadiyah Gresik, 2024)
Understanding students' perceptions of teachers' language choices is crucial as it significantly impacts motivation, allowing educators to cater to diverse student abilities and address learning difficulties. Effective preparation, encompassing materials and teaching methods, becomes indispensable in fostering support for learning. Constructivist theories by Piaget and Vygotsky underscore teachers as facilitators, guiding students through active interaction and collaboration to construct knowledge. This research delves into examining the correlation between students' perceptions of teachers' use of a second language in teaching English and their motivation to learn English. Employing a quantitative approach, the study involved 37 junior high school students from Muhammadiyah 4 Giri in Gresik, with data collected through a closed-ended questionnaire. Data analysis results reveal a positive and significant correlation between students' perceptions of teachers' use of a second language, specifically Indonesian as the medium of instruction, and their motivation to learn English. This implies that more positive perceptions regarding the use of a second language by teachers correspond to higher motivation levels for learning English. These findings underscore the pivotal role of the second language in junior high school English teaching. Teachers may consider employing Indonesian strategically to enhance students' motivation to learn English. Future research is recommended to delve deeper into understanding additional factors influencing the correlation between students' perceptions, teachers' language choices, and students' motivation. Expanding the sample size and including diverse school contexts can further enhance the generalizability of the results.